Geographic overlap and acquisition pairing - Chen, Zhuo; Kale, Prashant; Hoskisson, Robert E. (Strategic Management Journal, 2018)
Research Summary : This study examines the role of geographic factors in explaining acquisition pairing using a novel conditional logic methodology. Drawing from information asymmetry arguments regarding acquisition decisions, we theorize that geographic overlap between the acquirer and potential targets’ businesses and operations enables the acquirer to collect more information about the potential target through its multiple business operations that are geographically proximate. We also demonstrate moderating boundary conditions. In particular, we examine acquiring firm characteristics, acquiring firm size and geographic dispersion, which both weaken the relationship between geographic overlap and acquisition pairing. Likewise, we examine two dyadic distance moderators, geographic distance and product dissimilarity, both of which increase information asymmetry between the acquirer and potential targets, which increases the effect of geographic overlap in facilitating acquisition pairing. Managerial Summary : Firms pursuing acquisition activities face severe information asymmetry when evaluating potential targets. This study investigates how acquiring firms leverage geographic conditions to overcome information asymmetry and choose targets that they can better evaluate. We find that acquirers are more likely to choose targets that have subsidiaries or business operations overlapping in the same states as the acquirers themselves. This is particularly true for small acquirers, which lack resources and capabilities to seek external assistance, and acquirers that have business operations in more concentrated locations. We also find that acquiring targets with geographically overlapped business operations is especially salient when the target's headquarters is distantly located from the acquirer or when the target offers dissimilar products from the acquirer.